Clustering of Slovenian Municipalities - Melita Hajdinjak, Melita Hajdinjak (Anali PAZU, 2022)
We observe the municipalities of Slovenia as objects with different statistical properties and classify them into groups or clusters according to several related properties. The existence, number and structure of clusters show differences and similarities between municipalities as well as a centralization or marginalization of the Slovenian territory. The obtained categorization of municipalities is made of clearly separated groups, in which the north-eastern part of Slovenia, especially Pomurje, shows a »negative« position. Our results could help linking the municipalities into reasonable bigger regions.